Platelets: New Bricks in the Building of Neutrophil Extracellular Traps - Carestia, Agostina; Kaufman, Tomas; Schattner, Mirta (Frontiers in Immunology, 2016)
In addition to being key elements in hemostasis and thrombosis, platelets have an important role in the inflammatory and innate immune response. This activity is associated with their capability to recognize pathogens trough the expression of Toll like receptors, the secretion of a wide variety of cytokines, chemokines and growth factors stored within their granules and the expression of cell adhesion molecules that allows interaction with other immune cells, mainly neutrophils and monocytes. As part of the first line of defense, neutrophils control invading pathogens by phagocytosis, the release of antimicrobial proteins during degranulation or through the formation of web-like structures named neutrophil extracellular traps (NETs). NETs are formed by chromatin, proteases and antimicrobial proteins and their main function is to trap and kill bacteria, virus and fungi, avoiding their dissemination. Besides microorganisms, NET formation is also triggered by proinflammatory molecules, and platelets. The uncontrolled formation of NETs might exert tissue damage and has been involved as a pathogenic mechanism of autoinmune and prothrombotic clinical conditions. In this review, we discuss the role of platelets in NET generation highlighting the mediators, stimuli and molecular mechanisms involved in this phenomenon, both in human and murine models.